Performance evaluation of dynamic reconfiguration in high-speed local area networks - Casado, R.; Bermudez, A.; Quiles, F.J.; Sanchez, J.L.; Duato, J. (6th International Symposium on High-Performance Computer Architecture: Proceedings HPCA-6, January 8-12, 2000, Toulouse, France, 2000)
High-speed local area networks (LANs) consist of a set of switches connected by point-to-point links, and hosts linked to switches through a network interface card. High-speed LANs may change their topology due to switches and hosts being turned on/off, link remapping, and component failures. In these cases, a distributed reconfiguration algorithm analyzes the topology, computes the new routing tables, and downloads them to the corresponding switches. Unfortunately, in most cases, user traffic is stopped during the reconfiguration process to avoid deadlock. Although network reconfigurations are not frequent, static reconfiguration such as this may take hundreds of milliseconds to execute, thus degrading system availability significantly. In this paper, we propose a new deadlock-free distributed reconfiguration algorithm that is able to asynchronously update routing tables without stopping user traffic. This algorithm is valid for any topology, including regular as well as irregular topologies. Simulation results show that the behavior of our algorithm is significantly better than for other algorithms based on a spanning-tree formation.